1998
DOI: 10.1038/bjc.1998.126
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutation is a poor prognostic indicator for survival in patients with hepatocellular carcinoma undergoing surgical tumour ablation

Abstract: Summary Forty-two patients with hepatocellular carcinoma (HCC) were resected and their tumours were analysed for p53 mutations by GCclamped denaturing gradient gel electrophoresis (DGGE), single-strand conformation polymorphism (SSCP) and gene sequencing. All the exons have been analysed in this study. Eight of 12 HCCs with cirrhosis due to viral hepatitis and the two patients with sarcomatoid changes displayed p53 mutations. In contrast, no mutation was observed in the fibrolamellar variant (n = 9), non-cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
57
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 23 publications
5
57
1
1
Order By: Relevance
“…[4][5][6] Likewise, mutations in key genes such as TP53 and CTNNB1 (betacatenin), which are routinely identified in a proportion of typical hepatocellular carcinomas, have not been found in fibrolamellar carcinoma. [7][8][9] The limited chromosomal instability and the lack of mutations in key genes found in hepatocellular carcinoma raised the possibility that epigenetic changes, such as methylation of tumor suppressor gene promoters, may play a prominent role in the etiology of fibrolamellar carcinomas. Thus, we sought to explore the role of methylation by examining a panel of tumor suppressor gene promoters in fibrolamellar carcinomas and comparing the frequency of methylation to two control groups: hepatocellular carcinomas arising in cirrhotic livers and hepatocellular carcinomas arising in non-cirrhotic livers without evidence for chronic liver disease.…”
mentioning
confidence: 99%
“…[4][5][6] Likewise, mutations in key genes such as TP53 and CTNNB1 (betacatenin), which are routinely identified in a proportion of typical hepatocellular carcinomas, have not been found in fibrolamellar carcinoma. [7][8][9] The limited chromosomal instability and the lack of mutations in key genes found in hepatocellular carcinoma raised the possibility that epigenetic changes, such as methylation of tumor suppressor gene promoters, may play a prominent role in the etiology of fibrolamellar carcinomas. Thus, we sought to explore the role of methylation by examining a panel of tumor suppressor gene promoters in fibrolamellar carcinomas and comparing the frequency of methylation to two control groups: hepatocellular carcinomas arising in cirrhotic livers and hepatocellular carcinomas arising in non-cirrhotic livers without evidence for chronic liver disease.…”
mentioning
confidence: 99%
“…Many studies have shown that p53 is frequently mutated in human hepatocellular carcinoma (HCC). [2][3][4][5] Although altered p53 expression has been reported to correlate with advanced tumor grade, progression, therapy, and survival, 4 -7 information on how the mutations in the p53 gene is linked to recurrence of HCC is limited and the expression of ZBP-89, a four-zinc finger transcription factor that regulates the expression of several genes related to cell growth through binding to GC-rich DNA elements, 11 has not been reported in HCC. HCC is an extremely aggressive disease and the mortality of this disease is very high.…”
mentioning
confidence: 99%
“…5 wt-p53 is a component of one of the pathways activated in response to DNA damage, [6][7] and is involved in several different aspects of cell cycle arrest, apoptosis, control of genome integrity, and DNA repair. 8 Many studies have shown that p53 is frequently mutated in HCCs, [9][10][11] and the frequency and type of abnormality/ mutation are associated with predisposing factors and geographic area. p53 Mutation is linked with the progression of HCC from an early to a more advanced stage; the primary lesion is composed of genetically heterogeneous subclones, consistent with steps in multistage tumor progression.…”
mentioning
confidence: 99%